Strangers at Home? Informal Hosting of Undocumented Migrants and the Ambivalences of Encounter, Compassion, and Care in the Private Sphere - Saltiel, Rivka (Frontiers in Political Science, 2022)
Through a feminist care ethics lens, this paper explores the particular caring relations of Hébergement, an informal hosting initiative for transitory undocumented migrants in Brussels. It elaborates on how the intimate, private setting of hosting at home affects a caring-with relationship. Hosting and being hosted significantly differs from other forms of shelter and migrant (or homeless) support. There is no script for this particular social constellation. Hosting requires trust and a great deal of physical and emotional labor of all involved and often leads to exhaustion. Being together in and sharing the intimate space of the home entails a continuous negotiation of—sometimes conflicting—needs (for space, intimacy, distance, self-care, etc.) of all at home. The informal caring arrangements and the resulting relations of Hébergement are ambivalent and are understood as yet another expression of the lack of sufficient and adequate caring resources on a societal level (‘care crisis’). With its fundamentally relational approach, feminist care ethics unravel the uneven structures that permeate and define both the practice of care and caring relations. Thereby, it challenges the structural organization of care in capitalism that is exclusive, racialized, inherently feminized, domesticized, privatized, and individualized and envisions an alternative, more just social organization of care—in a caring-with society. Drawing on narrative interviews, the paper explores how strangers encounter each other ‘at home’, how they care-with each other, and how they address the potentials, ambivalences, and limits of hosting and caring-with strangers at home.